Defects in Intervertebral Disc and Spine During Development, Degeneration, and Pain: New Research Directions for Disc Regeneration and Therapy - Mohanty, Sarthak (Wiley Interdiscip Rev Dev Biol, 2019)
Intervertebral discs are cartilaginous joints present between vertebrae. The centers of the intervertebral discs consist of a gelatinous nucleus pulposus derived from the embryonic notochord. With age or injury, intervertebral discs may degenerate, causing neurological symptoms including back pain, which affects millions of people worldwide. Back pain is a multifactorial disorder, and disc degeneration is one of the primary contributing factors. Recent studies in mice have identified the key molecules involved in the formation of intervertebral discs. Several of these key molecules including sonic hedgehog and Brachyury are not only expressed by notochord during development, but are also expressed by neonatal mouse nucleus pulposus cells, and are crucial for postnatal disc maintenance. These findings suggest that intrinsic signals in each disc may maintain the nucleus pulposus microenvironment. However, since expression of these developmental signals declines with age and degeneration, disc degeneration may be related to the loss of these intrinsic signals. In addition, findings from mouse and other mammalian models have identified similarities between the patterning capabilities of the embryonic notochord and young nucleus pulposus cells, suggesting that mouse is a suitable model system to understand disc development and aging. Future research aimed at understanding the upstream regulators of these developmental signals and the modes by which they regulate disc growth and maintenance will likely provide mechanistic insights into disc growth and aging. Further, such findings will likely provide insights relevant to the development of effective therapies for treatment of back pain and reversing the disc degenerative process.